(untitled) (Research, Society and Development, 2021)
The main objective of this study is to assess the reuse of naturally old ballast that was removed from an operating railroad. In order to verify the viability of its reuse, laboratory tests were carried out, based on the procedures and parameters established in literature. The reuse of ballast would reduce costs, minimize the disposal of this material and reduce quarry extraction. There are several standards regulations the ballast’s (gravel) properties, such as size, shape, hardness, abrasion resistance and composition to provide better performance of the rail platform, due to the wide variety of materials and environmental conditions to which they are subjected. Ballast specifications are based on the execution of characterization tests and can be divided according to strength properties and geometric properties. Thus, several specifications have been used by different railway organizations around the world to meet the needs of their projects. One test used to analyze ballast quality is the Los Angeles Abrasion, which provides data on resistance to fragmentation. The durability of the ballast depends on the quality of the gravel related to the original rock composition. This is an important parameter that can be associated with railroad maintenance, which is expensive. A series of tests were carried out to evaluate the ballast properties, as well as an analysis of the geometric and mineralogical characteristics of the gravel, and the impact of the variation of these properties in the performance of the ballast. The viability of reusing the ballast removed from an operating road was then evaluated, and it was concluded that the material is still suitable for reusing, although its properties have undergone a few changes, without modifying its main characteristics and functions.